Two decades of spice trade among SAFTA nations - Is it really aromatic for India? - Kalpana, E N; Shivakumar, K M; Vidhyavathi, A; Mahendran, K; Jagadeeswaran, R; Kalpana, M (Plant Science Today, 2025)
Regional Trade Agreements (RTAs) are the foundation of the multilateral trading mechanism and act as a path to boost trade, enhance market access and strengthen relations with economies across the globe. The growing number of trade agreements between countries and within regions reflects a global momentum towards economic openness and creating more dynamic and competitive market environments. This study employs the gravity model with panel data from 2002 to 2020 to examine the trade effects, including trade creation and trade diversion of the Free Trade Agreement (FTA) on the spices trading between India and SAARC member countries under the South Asian Free Trade Agreement (SAFTA). The analysis shows a trade creation effect of SAFTA in the fixed effect (FE) model. The results also suggest that the spice trade could help in improving the Indian economy with SAFTA. India being the major spice exporter to the world nations and SAARC countries, has the relative trade advantage in spice trade with members of SAARC nations. Globally, India can use the advantage of exporting spices for higher value rather than for high volume proportional to the distance, which is a proxy for the trade costs.